Using a comfort zone model and daily life situations to develop entrepreneurial competencies and an entrepreneurial mindset - Van Gelderen, Marco (Frontiers in Psychology, 2023)
This article presents a novel experiential learning format that aims to develop participants' entrepreneurial competencies and entrepreneurial mindset. Furthermore, this study investigates factors that promote individuals' competency development and mindset formation when using this learning format. In this format, students practice enterprising behavior in daily life, rather than by starting a venture. Teams of participants receive a set of eight to 10 challenges. Each challenge asks participants to create value for other people. The challenges are not revealed until the exercise starts, and they are worked on for 1 or 2 days full-time. Each challenge allows participants to practice the competencies of generating ideas for opportunities, taking action, perseverance, networking and network utilization, teamwork, and convincing others. Collectively, this contributes to developing an enterprising mindset. This format is based on a comfort zone model and aims to promote significant learning in a short time. After a week, each participant submits a reflection on their actions during the experiential part. In this study, we analyze the experiences of 198 participating students from six courses in five countries to bring out the factors that contribute to students staying in versus leaving their comfort zone, and the types of learning which result. Learning occurs when participants leave their comfort zone and have experiences that surprise them, leading to novel realizations. Key to learning is the element of surprise.